(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Lattakia is witnessing a significant increase in the size of population, recording 991,000 people in 2011, in an area of 2290 sq.km, leading to high population density amounting to 432.7 people per sq.km. Thus, the increasing size of population and the consequent growth in parallel in population’s needs for jobs, water, housing and services of all kinds, and the lack of sufficient economic resources to meet these needs have resulted in a set of problems created in the province: imbalance in population distribution, because two thirds of the population in lattakia live in an area of about (40%) of Lattakia which is a civil, administrative center and an important port. All that led to pressures on the governorate of Latakia that created economic and social problems, like increasing unemployment rate due to huge demand on job opportunities , in addition to wasting and inefficient investment of water resources reducing the per capita share of water from (78.8) thousand cubic meters yearly in 2004, to (74.2) thousand cubic meters in 2011. Finally, the increase in population was not accompanied with an increase in the cultivated area So it has led to pressure on agricultural production causing food insecurity. Therefore, this study is considered a scientific work which can be a guide when planning programs and social and development plans at the level of the province of Lattakia.